2021
DOI: 10.3892/ol.2021.13071
|View full text |Cite
|
Sign up to set email alerts
|

CTBP1 strengthens the cisplatin resistance of gastric cancer cells by upregulating RAD51 expression

Abstract: Drug resistance is a key factor affecting the treatment of gastric cancer. The resistance of gastric cancer cells to anticancer drugs, such as cisplatin (DDP), remains a major challenge to patient recovery. The present study aimed to investigate the roles of C-terminal-binding protein 1 (CTBP1) in the DDP resistance of gastric cancer cells and to determine its regulatory effect on DNA repair protein RAD51 homolog 1 (RAD51). The DDP-resistant human gastric cancer AGS and HGC cell lines, AGS/DDP and HGC-27/DDP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Inactivation or low expression of HRR-related genes is frequently observed in breast cancer cells and might lead to HRD ( 21 ). Considering the documented functions of HRR-related proteins in human breast cancer cells ( 22 24 ), we performed an immunoblot analysis with cells treated with GDP-M. We observed that BRCA2 expression was reduced, whereas the expression of other HRR-related proteins was not significantly affected (Fig. 4B and fig.…”
Section: Resultsmentioning
confidence: 95%
“…Inactivation or low expression of HRR-related genes is frequently observed in breast cancer cells and might lead to HRD ( 21 ). Considering the documented functions of HRR-related proteins in human breast cancer cells ( 22 24 ), we performed an immunoblot analysis with cells treated with GDP-M. We observed that BRCA2 expression was reduced, whereas the expression of other HRR-related proteins was not significantly affected (Fig. 4B and fig.…”
Section: Resultsmentioning
confidence: 95%
“…CTBP1 is a transcriptional regulator of a range of developmental processes and promotes cancer progression. 202 , 203 , 204 , 205 However, its role in T cell differentiation is unknown. Our transcriptomic data suggest that upon chronic stimulation, Ctbp1 inactivation pushes cells into a relatively active state accompanied by stalled terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The most common mutations in the HR pathway occur in the BRCA1, BRCA2, RAD51, BLM, and RAD50 genes [ 74 ]. RAD51 overexpression has been linked to worse prognosis in patients with sporadic gastric cancer and neuroblastoma who present modified MRE11 [ 75 , 76 ]. In contrast, RAD50 and NBS1 mutations are associated with carcinogenesis during endometrial and prostate cancer development [ 77 , 78 ].…”
Section: Double-strand Break (Dsb) Repairmentioning
confidence: 99%